A Ferrocene–Tryptophan Conjugate: The Role of the Indolic Nitrogen in Supramolecular Assembly. Issue 10 (24th October 2017) - Falcone, Natashya; Basak, Shibaji; Dong, Bin; Syed, Jebriel; Ferranco, Annaleizle; Lough, Alan; She, Zhe; Kraatz, Heinz‐Bernhard
Abstract: Bio‐organometallic ferrocene‐containing amino acids and peptides have been reported to form gels and are interesting to study due to their structural properties and applications for biological purposes. In this study, a ferrocene‐dicarboxylic acid derivative of the dipeptide tryptophan–tryptophan was investigated. The indolic nitrogen in the amino acid tryptophan is important for biological functions due to its role in hydrogen bonding. Here, intermolecular interactions with the indolic nitrogen allow this conjugate to self‐assemble into a fibrous supramolecular structure that forms a stable gel. Rheological analysis demonstrates the self‐healing nature of this gel. Interestingly, X‐ray analysis of this ferrocene–peptide conjugate reveals close contacts involving tryptophan, in particular the indole NH group in interactions with an adjacent neighboring molecule. Abstract : Packing for two : A ferrocene‐dicarboxylic acid derivative of tryptophan–tryptophan was synthesized and shown to assemble into a supramolecular gel (see figure). The intermolecular hydrogen bonding revealed by X‐ray crystallography provides insight into the packing and the molecular interactions responsible for the formation of a nanofibril network structure (see figure).